Detection of Anti-Paracoccidioides brasiliensis antibodies in suspected tuberculosis patients = Detecção de anticorpos anti-Paracoccidioides brasiliensis em pacientes suspeitos de tuberculose - Maria Luiza Dias Fraga Peron; Terezinha Inez Estivalet Svidzinski; Jorge Juarez Vieira Teixeira; Cristina Padre Cardoso; Fernanda Luiza Espinosa Spositto; Rosilene Fressatti Cardoso (Acta Scientiarum. Health Sciences, 2010)
Paracoccidioidomycosis (PCM) is an important systemic mycosis in LatinAmerica that occurs as active disease in 1-2% of Paracoccidioides brasiliensis infected people. Like PCM, tuberculosis (TB) affects mainly the lungs and the clinical and radiological aspects do notalways allow differentiation between them. The aim of this study was to carry out serological investigation for detecting anti-P. brasiliensis antibodies, by three serological methods, in patientswith symptoms suggestive of pulmonary TB. From August 2005 to September 2006, 76 patients with pulmonary symptoms suspected for TB were attended at the Regional Specialties Center Laboratory in the city of Paranavaí, Paraná, Brazil and submitted to microbiological TB research, ELISA, immunodiffusion and immunoblotting for PCM. Of all the individuals, 21 (27.63%) were reactive to P. brasiliensis by ELISA and 11 (14.47%) showed a laboratory diagnosis of pulmonary TB. Of all the individuals serologically reactive to P. brasiliensis, by ELISA, none had positive results by immunodiffusion and one reacted with antigen 43 kDa when Immunobloting was carried out. Our results lead us to reflect a necessity to obtain a more specific serologic test for diagnosis of PCM disease in patients with respiratory symptoms considering the high number of individuals reactive to P. brasiliensis especially in endemic areas. Paracoccidioidomicose (PCM) é importante micose sistêmica na América Latina, que ocorre como doença ativa em 1-2% dos indivíduos infectados com Paracoccidioides brasiliensis. Assim como a PCM, a tuberculose (TB) afeta principalmente os pulmões, porém os aspectos clínicos e radiológicos nem sempre permitem a diferenciação entreessas doenças. O objetivo deste estudo foi realizar um inquérito sorológico para a detecção de anticorpos anti-P. brasiliensis, utilizando três métodos sorológicos, em pacientes com sintomassugestivos de tuberculose pulmonar. De agosto de 2005 a setembro de 2006, 76 pacientes sintomáticos foram atendidos no Laboratório do Centro Regional de Especialidades de Paranavaí, Paraná, Brasil e submetidos à investigação microbiológica para TB e de anticorpos por ELISA, imunodifusão e immunobloting para PCM. Destes, 21 (27,63%) foram reativos para P. brasiliensis por ELISA e 11 (14,47%) apresentaram diagnóstico laboratorial de tuberculose pulmonar. Dosindivíduos sorologicamente reativos para P. brasiliensis, por ELISA, nenhum apresentou resultado positivo pela técnica de imunodifusão e um reagiu com antígeno de 43 kDa quando do uso de immunobloting. Os resultados obtidos nos levam a refletir da necessidade de se obter um teste sorológico mais específico para o diagnóstico de PCM doença em pacientes com sintomas respiratórios, considerando o elevado número de indivíduos reativos para P. brasiliensis principalmente em áreas endêmicas.